# Math, derivatives

posted by .

f(x) = x² + 2Cos²x, find f ' (x)

a) 2(x+cos x)
b) x - sin x
c) 2x + sin x
d)2(x - sin2x)

I got neither of these answers, since the 2nd part should be chain rule, right?

f(x) = x² + 2Cos²x = x² + 2(Cos x)²
then f '(x) = (2)(2)(cosx)(-sinx)
f '(x) = 2x - 4cosxsinx

If I do it this way, then I get that the answer is d:
f(x) = x² + 2Cos²x
f '(x) = x² + 2(-sin x)²
f '(x) = 2x - 2sin²x
f '(x) = 2(x - sin²x)

Is that how I should be doing it?

• Math, derivatives -

sorry, this part:
then f '(x) = (2)(2)(cosx)(-sinx)

should say:

then f '(x) = 2x + (2)(2)(cosx)(-sinx)

• Math, derivatives -

You're on the right track.

sin 2x= 2sin x cos x (identity)
f'(x)=2x-2(sin2x)
f'(x)=2(x-sin2x)

• Math, derivatives -

Thanks for your reply! That makes much more sense now. I guess I should go and review my identities.

## Similar Questions

1. ### calc

Where do I start to prove this identity: sinx/cosx= 1-cos2x/sin2x please help!! Hint: Fractions are evil. Get rid of them. Well, cos2x = cos 2 x - sin 2 x, so 1-coscx = 1 - cos 2 x - sin 2 x = 1 - cos 2 x + sin 2 x You should be able …
2. ### tigonometry

expres the following as sums and differences of sines or cosines cos8t * sin2t sin(a+b) = sin(a)cos(b) + cos(a)sin(b) replacing by by -b and using that cos(-b)= cos(b) sin(-b)= -sin(b) gives: sin(a-b) = sin(a)cos(b) - cos(a)sin(b) …
3. ### Trig

Given: cos u = 3/5; 0 < u < pi/2 cos v = 5/13; 3pi/2 < v < 2pi Find: sin (v + u) cos (v - u) tan (v + u) First compute or list the cosine and sine of both u and v. Then use the combination rules sin (v + u) = sin u cos …

5. ### Mathematics - Trigonometric Identities

Let y represent theta Prove: 1 + 1/tan^2y = 1/sin^2y My Answer: LS: = 1 + 1/tan^2y = (sin^2y + cos^2y) + 1 /(sin^2y/cos^2y) = (sin^2y + cos^2y) + 1 x (cos^2y/sin^2y) = (sin^2y + cos^2y) + (sin^2y + cos^2y) (cos^2y/sin^2y) = (sin^2y …
6. ### Math - Solving Trig Equations

What am I doing wrong? Equation: sin2x = 2cos2x Answers: 90 and 270 .... My Work: 2sin(x)cos(x) = 2cos(2x) sin(x) cos(x) = cos(2x) sin(x) cos(x) = 2cos^2(x) - 1 cos(x) (+/-)\sqrt{1 - cos^2(x)} = 2cos^2(x) - 1 cos^2(x)(1 - cos^2(x))
7. ### TRIG!

Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6 x=1 - (3/4)sin^2 2x work on one side only! Responses Trig please help! - Reiny, Monday, February 23, 2009 at 4:27pm LS looks like the sum of cubes sin^6 x + cos^6 …
8. ### Math

the original problem was: (sin x + cos x)^2 + (sin x - cos x)^2 = 2 steps too please I got 1 for (sin x + cos x)^2 but then what does (sin x - cos x)^2 become since it's minus?
9. ### Calculus - please check my work

differentiate each function a) y = cos^3x b) y = sin(x^3) c) y = sin^2 xcos3x my answers: a) y' = 3cos^2 x(-sinx) b) y' = cos(x^3)(3x^2) c) for this one, i don't know which one is correct. i got 2 different answers but i think they …
10. ### Trigonometry

Solve the equation for solutions in the interval 0<=theta<2pi Problem 1. 3cot^2-4csc=1 My attempt: 3(cos^2/sin^2)-4/sin=1 3(cos^2/sin^2) - 4sin/sin^2 = 1 3cos^2 -4sin =sin^2 3cos^2-(1-cos^2) =4sin 4cos^2 -1 =4sin Cos^2 - sin=1/4 …

More Similar Questions